EDUCATION CONCEPT AND ITS RELATION TO GROWTH ECONOMIC IN THE UE-28 (Dimensión Empresarial, 2019)
ABSTRACTThe first theoretical analyzes on the correlation between education and economic growth were supported by Theodore Schultz, Edward Deninson and Gary Becker, during the decade of the 60s. The study of the interconnections between these variables is determined by the Economics of Education, the which analyzes in detail what are the main actions taken by the nation states on the education sector and its consequences on the economic growth of a society.